2002
DOI: 10.1002/macp.200290003
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Refractive Index Change of Polymer Films Containing Mesoionic Sulfur‐Substituted Phenyloxatriazolones

Abstract: We measured photoinduced refractive index changes (see Figure) of polymer films containing various sulfur‐containing mesoionic compounds. PMMA films containing 30 wt.‐% of 3‐phenyl‐1,2,3,4‐thiatriazole‐5‐thione (3PTTT) showed refractive index changes of −0.036 during photoirradiation, at a wavelength far from the resonant region. An increase in the number of sulfur atoms in the mesoionic compounds doped in PMMA films resulted in the increase in refractive index changes during photoirradiation. The estimation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…[1][2][3] Recently, much attention has been devoted to the photochemical control of refractive indices for polymer films, owing to their potential in optical network technology. 3 Although there are extensive studies directed toward a photoinduced decrease in refractive indices for polymer films, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] only a few attempts have been made to enhance the refractive index through photochemical transformations. 12,[20][21][22][23][24][25] For example, Langer et al 21 reported that irradiation of a polymerbearing thiocyanate pendants enhanced the refractive index (n) of the polymer by 0.031.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, much attention has been devoted to the photochemical control of refractive indices for polymer films, owing to their potential in optical network technology. 3 Although there are extensive studies directed toward a photoinduced decrease in refractive indices for polymer films, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] only a few attempts have been made to enhance the refractive index through photochemical transformations. 12,[20][21][22][23][24][25] For example, Langer et al 21 reported that irradiation of a polymerbearing thiocyanate pendants enhanced the refractive index (n) of the polymer by 0.031.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hands, by using irreversible photochemical reactions such as photoelimination and photopolymerization, large refractive index changes of polymer films have been realized with transparency both before and after photoirradiation in a wide visible region. [10][11][12][13][14][15][16][17][18][19] Among them, Photoelimination brings about the changes not only in electronic structure of photoreactive compounds and also in the density of the polymer films, which leads to larger refractive index changes. 16,17 The refractive indices of the photoirradiated area decreased in many cases, however, the increases in refractive index of the photoirradiated area are necessary for some applications.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain stable, easy to handle, film-forming materials, the photoreactive mesoionic group must be covalently attached to a polymer. During the last several years we have described the synthesis and polymerization behavior of various styrene substituted mesoionic 6-oxo-1,6-dihydropyrimidin-3-ium-4-olates. Recently, different methods for the synthesis of polymerizable mesoionic methacryl derivatives have also been developed. , We also prepared polymers that are based on phenols as the polymerizable group or polycondensates bearing mesoionic groups in the main chain. , An alternative method is to modify technical polymers with dispersed crystals of photosensitive mesoions …”
Section: Introductionmentioning
confidence: 99%
“…For the estimation of changes in the physical properties by irradiation, different methods have been developed. For example, waveguide-mode spectroscopy can be used to determine changes in the refractive index and film thickness of spin-coated polymer films. ,, Other methods involve changes in the solubility or spectroscopic characteristics. , …”
Section: Introductionmentioning
confidence: 99%